1966
DOI: 10.1177/004051756603600101
|View full text |Cite
|
Sign up to set email alerts
|

The Estimation of Mothproofing Agents in Wool

Abstract: Techniques for the removal of dieldrin from wool are compared and methods of analysis are described. A culorimetric method [19] is satisfactory, when proceeded by prior cleanup of the extract. Gas chromatography on a silicone oil column, without any preliminary cleanup, gives an excellent separation of dietdrin. This method has been used to measure fastness properties of dieldrin-treated wool, and data obtained earlier with radioactive dieldrin [28] have been confirmed.' The gas chromatographic procedure may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1966
1966
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Analyses [28] showed only small variations in initial insecticide content and similar amounts removed during subsequent washing. W hen tested after washing, the addition of the pyrethrum synergists piperonyl hutoxide, MGK 264 ( N-( 2-ethylhexyl ) -bicyclo ( 2.2.1 ) -hept-5-ene-2,3-dicarboximide [ 12] ) or sulfoxide ( 1,2-methylene dioxy-4-( 2-( octylsulfinyl ) propyl ) benzene [ 12 ] ) had no beneficial effect on insectproofing with Dilene.…”
Section: Organic Phosphorus Compoundsmentioning
confidence: 90%
See 2 more Smart Citations
“…Analyses [28] showed only small variations in initial insecticide content and similar amounts removed during subsequent washing. W hen tested after washing, the addition of the pyrethrum synergists piperonyl hutoxide, MGK 264 ( N-( 2-ethylhexyl ) -bicyclo ( 2.2.1 ) -hept-5-ene-2,3-dicarboximide [ 12] ) or sulfoxide ( 1,2-methylene dioxy-4-( 2-( octylsulfinyl ) propyl ) benzene [ 12 ] ) had no beneficial effect on insectproofing with Dilene.…”
Section: Organic Phosphorus Compoundsmentioning
confidence: 90%
“…probably by elution of the active insecticide by the alkaline washing liquors, rather than its inactivation. In an accompanying paper [28] the actual contents of DDT and Dilene have been determined in detail, and the greater durability of the insectproofing with Dilene is due to this compound having inherently letter fastness properties on wool than does DDT.…”
Section: Organic Phosphorus Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum concentrations required for effective mothproofing given there [ 11 ] were nominal and gas chromatography (again using the conditions described hy Williams [14]. which gave elution of a main peak at 1.50 .min) has now shown that these are in fact about 0.07% for Anthrenus and 0.10% for Tineola.…”
Section: Introductionmentioning
confidence: 99%